Aqueous Extract of Prosopis strombulifera (LAM) BENTH Induces Cytotoxic Effects against tumor Cell Lines without Systemic Alterations in BALB/c Mice - Hapon, María Belén (2014)
Prosopis strombulifera (Lam.) Benth. is a rhizomatous shrub native to the northern and central zones of Argentina. The analgesic and antibiotic properties of this plant had been demonstrated but there are no previous reports of its cytotoxic activity. The goal of this work was to analyze the cytotoxic activity of P. strombulifera against HCT-116 and MCF-7 cell lines, and to evaluate toxic systemic effects in BALB/c mice. Changes induced by the aqueous extract from leaves on tumoral cell lines were studied by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5 diphenyltetrazolium bromide) tetrazolium reduction assay, Trypan blue dye exclusion assay, optical microscopy, Western Blot analysis of PCNA and cPARP, LDH activity, Ames´ test and clonogenic survival. Oral sub-chronic toxicity was assessed on BALB/c mice at concentrations up to 150 mg/animal/day. Analyses included animal/organs weight; erythrocytes, leukocytes and platelets number; and serological determinations of glucose, ASAT, ALAT, urea and creatinine. Extract has induced cytotoxicity, affecting proliferation and viability in both cell lines in a dose and time-response manner. IC50 was 2.25 μg/ml and LC50 5.05 μg/ml in HCT-116, while values were 3.01 μg/ml and 7.52 μg/ml, respectively, in MCF-7. In both cell lines, the antiproliferative effect was confirmed by reduction of PCNA protein expression. When LC50 concentrations were used, extract-induced necrosis (evidenced by the increase in extracellular LDH activity), apoptosis (increased cPARP protein expression) and clonogenic survival diminution. Mutagenic activity of extract was caused at concentrations of 500 μg/ml (99 and 64-fold higher than HCT-116 and MCF-7 LC50 concentrations). Animal studies demonstrated that no significant toxicity was induced. In conclusion, this is the first report of P. strombulifera cytotoxic activity against tumoral cell lines. Sub-chronic extract administration did not cause deleterious effects in vivo. Altogether, the presented results make P. strombulifera a promising natural product for cancer research and treatment.